Enhancement of Energy Harvesting Performance by a Coupled Bluff Splitter Body and PVEH Plate through Vortex Induced Vibration near Resonance - Chin, W.K.; Ong, Z.C.; Kong, K.K.; Khoo, S.Y.; Huang, Y.H.; Chong, W.T. (MDPI, 2017)
Inspired by vortex induced vibration energy harvesting development as a new source of renewable energy, a T-shaped design vibration energy harvester is introduced with the aim of enhancing its performance through vortex induced vibration at near resonance conditions. The T-shaped structural model designed consists of a fixed boundary aluminum bluff splitter body coupled with a cantilever piezoelectric vibration energy harvesters (PVEH) plate model which is a piezoelectric bimorph plate made of a brass plate sandwiched between 2 lead zirconate titanate (PZT) plates. A 3-dimensional Fluid-Structure Interaction simulation analysis is carried out with Reynolds Stress Turbulence Model under wind speed of 7, 10, 12, 14, 16, 18, 19, 20, 22.5, and 25 m/s. The results showed that with 19 m/s wind speed, the model generates 75.758 Hz of vortex frequency near to the structural model's natural frequency of 76.9 Hz. Resonance lock-in therefore occurred, generating a maximum displacement amplitude of 2.09 mm or a 49.76% increment relatively in vibrational amplitude. Under the effect of resonance at the PVEH plate's fundamental natural frequency, it is able to generate the largest normalized power of 13.44 mW/cm3g2.